Nosocomial Citrobacter Infection in Neonatal Intensive Care Unit in a Hospital of Nepal - Khadka, Sanu Bhai; Thapa, Badri; Mahat, Kishori (Journal of Nepal Paediatric Society, 2011)
Introduction: Neonatal Citrobacter infection is either acquired horizontally or vertically as a nosocomial infection. The source of nosocomial Citrobacter is either hands of medical staff or the innate objects. Objective: The aim of this study was to study nosocomial Citrobacter infection in neonates admitted in Neonatal Intensive Care Unit (NICU) and trace the source of infection. Methods: The study was conducted in NICU in a hospital in Kathmandu, Nepal during a period of January to March 2010. Specimens were collected from neonates, hands of medical staff and innate objects and were processed using a standard microbiological method. Results: The prevalence of neonatal nosocomial infection was 32.6% (29/89). Citrobacter spp. was isolated in 11 neonates admitted in NICU with the prevalence rate of 37.9% (11/29) among other pathogens. Umbilical cord infection was most common (n=8). These isolates were grouped into five antibiotypes (I, 4; II, 3; III, 2; IV, I; V, 1). All of these isolates were multi-drug resistant showing susceptibility towards quinolones. The isolate of Citrobacter spp. was also recovered from a nasal prong which was grouped with 4 other clinical strains. Conclusion: Multi-drug resistant nosocomial Citrobacter spp. was inflicting neonates in NICU and the source of this pathogen was traced to nasal prong. Nosocomial Citrobacter infection is a common problem of neonates in NICU. This will lead to increase neonatal mortality if infection prevention and control practices are not initiated. Key words: Neonates; Citrobacter spp.; nasal prong; infection control; Nepal DOI: 10.3126/jnps.v31i2.4094 J Nep Paedtr Soc 2010;31(2):105-109